2021
DOI: 10.1101/2021.06.11.448071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced Hippocampal Inhibition and Enhanced Autism-Epilepsy Comorbidity in Mice Lacking Neuropilin 2

Abstract: The neuropilin receptors and their secreted semaphorin ligands play key roles in brain circuit development by regulating numerous crucial neuronal processes, including the maturation of synapses and migration of GABAergic interneurons. Consistent with its developmental roles, the neuropilin 2 (Nrp2) locus contains polymorphisms in patients with autism spectrum disorder (ASD). Nrp2 deficient mice show autism-like behavioral deficits and propensity to develop seizures. In order to determine the pathophysiology i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 56 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…2A-F; cell count, control: 84.03±7.88; iCKO: 52.83±7.50, p=0.0426; t (6) =2.565 unpaired t-test). In the CA1 we observed a substantial 46.41% decrease in SOM+ neurons (cell count: control: 36.90±3.97; iCKO: 19.78±3.14 in n=5 mice each p=0.0004; t (24) =4.659 by two-way ANOVA with Bonferroni multiple comparison correction). Interestingly, there was an apparent reduction in SOM+ cells in the DG, but the difference did not reach statistical significance (p=0.385).…”
Section: Developmental Deletion Of Nrp2 In Interneuron Progenitors Re...mentioning
confidence: 81%
See 4 more Smart Citations
“…2A-F; cell count, control: 84.03±7.88; iCKO: 52.83±7.50, p=0.0426; t (6) =2.565 unpaired t-test). In the CA1 we observed a substantial 46.41% decrease in SOM+ neurons (cell count: control: 36.90±3.97; iCKO: 19.78±3.14 in n=5 mice each p=0.0004; t (24) =4.659 by two-way ANOVA with Bonferroni multiple comparison correction). Interestingly, there was an apparent reduction in SOM+ cells in the DG, but the difference did not reach statistical significance (p=0.385).…”
Section: Developmental Deletion Of Nrp2 In Interneuron Progenitors Re...mentioning
confidence: 81%
“…Importantly, Nrp2 is a candidate ASD gene on SFARI (Score 2) and polymorphisms in Nrp2 gene have been reported in patients with autistic syndromes (16,17). We previously demonstrated that global Nrp2 deletion results in a significant decrease in density of several MGE-derived interneuron subtypes in hippocampus and reduced hippocampal inhibition (24). However, the effects of selective embryonic Nrp2 deletion in MGE-derived interneuron precursors and its impact on hippocampal interneuron population and inhibition was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations